Dielectric Properties of Nano Crystalline Cobalt Substituted Lithium Ferrites by Citrate-gel Auto Combustion Method. (2016) - Aravind, G.; Nehru, B.; Vijaya Kumar, R.; Ravinder, D.
Abstract: Nano-Crystalline Cobalt substituted Lithium ferrites having the compositional formula [Li0.5 Fe0.5 ]1-x Cox  Fe2 O4 (where x=0.0, 0.2, 0.4, 0.6, 0.8 and, 1.0) were prepared by Citrate- Gel Auto Combustion method at low temperature (180°C). The prepared powder samples were sintered at 500°C for 4hours. X-ray diffraction (XRD) analysis reveals that all the samples posses a single phase cubic spinel structure. The surface morphology of the samples was observed by field emission scanning electron microscopy (FESEM). The dielectric parameters such as dielectric constant ( ε '), dielectric loss tangent (tan δ) and AC conductivity (σAC ) of the samples were studied as a function of frequency in the range of 20Hz to 2M Hz at room temperature using Agilent E 4980 Precession LCR Meter. The dielectric constant, loss tangent and AC conductivity (σAC ) of the samples show a normal dielectric behavior with frequency which reveals that the dispersion is due to the Maxwell-Wagner type interfacial polarization and hoping of electrons between the Fe +2 and Fe +3 ions.